Reseña de: Peel, Christine (trad.), Guta Lag. The Law of the Gotlanders. London. Viking Society For Northern Research, 2009. 280 pp. ISBN: 978-09-0352-179-2 - García Pimentel, José Miguel (Espacio Tiempo y Forma. Serie III, Historia Medieval, 2017)
Peel, Christine (trad.), Guta Lag. The Law of the Gotlanders. London. Viking Society For Northern Research, 2009. 280 pp. isbn: 978-09-0352-179-2